Visualization of the Macrophage's Dynamic in TB-HIV Co-Infection Using the Molecular Imaging Techniques: A Narrative Review - Fuad Minan Zuhri (Health Dynamics, 2024)
Introduction: Mycobacterium tuberculosis (Mtb) and human immunodeficiency virus (HIV) collaborate in order to weaken the immune system and increase the burden of both illnesses. Macrophages as the first intracellular niche against Mtb infection, are also involved in the persistence of the HIV infection, and may have an important role in the of tuberculosis (TB)-HIV co-infection. Improved knowledge of the macrophage function and pathogenesis dynamics may contribute to the development of newer and better diagnosis technique, prognosis assessment, and therapeutic intervention. By monitoring changes in the expression of molecular targets, macrophage identification methods that use molecular imaging techniques for cell image analysis can efficiently provide important information about macrophage biology and evaluate early response to therapy, which can facilitate medical personnel in the identification and treatment of TB-HIV disease. Methods: This study is a narrative review highlighting the utilization of molecular imaging techniques to capture macrophage dynamics in TB-HIV co-infection. Result and conclusion: Confocal laser scanning microscopy live imaging, flow cytometry, immunofluorescence microscopy, histochemical staining, scanning electron microscopy (SEM), and deconvolution microscopy images are among several molecular imaging techniques that can be used to visualize macrophage dynamics in TB-HIV co-infection.